1983
DOI: 10.1111/j.1365-2311.1983.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the susceptibility of tree species to attack by the gypsy moth, Lymantria dispar

Abstract: 1. Numbers of gypsy moth larvae feeding on each of 922 randomly sampled trees in a Quercus-Acer-Fraxinus forest in southwestern Quebec, Canada were counted in 1979 and in 1980 to quantify the larval feeding preferences as observed in the field for eighteen deciduous and one coniferous tree species at the northern range limit of the gypsy moth.2. Both the diameter at breast height (dbh) and the estimated foliage biomass of the sampled trees were used to calculate the relative proportions of foliage represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Many of the tree species belonging to families of Fagaceae, Salicaceae, Betulaceae and Rosasceae are the hosts throughout the native and invasive ranges (Lechowicz and Mauffette ; Pogue and Schaefer ). The preference of tree species by larvae varies considerably owing to the regional and local composition of the vegetation (Lechowicz and Jobin ; Mauffette et al. ; Mauffette and Lechowicz ).…”
Section: The Effects Of Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the tree species belonging to families of Fagaceae, Salicaceae, Betulaceae and Rosasceae are the hosts throughout the native and invasive ranges (Lechowicz and Mauffette ; Pogue and Schaefer ). The preference of tree species by larvae varies considerably owing to the regional and local composition of the vegetation (Lechowicz and Jobin ; Mauffette et al. ; Mauffette and Lechowicz ).…”
Section: The Effects Of Other Factorsmentioning
confidence: 99%
“…). Many hypotheses have been proposed to explain the host preferences of the gypsy moth in North America, for example, phylogeny (host trees in North America should be closely related to those in Europe), plant traits, dynamics of the gypsy moth and climatic conditions (Lechowicz and Jobin ; Montgomery ; Liebhold et al. ).…”
Section: The Effects Of Other Factorsmentioning
confidence: 99%
“…are considered resistant hosts because gypsy moth cannot complete development if larvae continuously feed on their leaves [12]. Although some studies have reported ash to be 'sporadically eaten' (reviewed in [2,13,14]) GML never caused visible canopy defoliation. Rejection of ash as a food plant is due to repellency induced by volatile deterrents [15] and feeding inhibition caused by harmful allelochemicals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Liebhold et al (1995~) have classified all tree species commonly occurring in North America as "susceptible," "resistant," or "immune" to gypsy moth defoliation, based on both laboratory and field experiments. For tree species in southern Quebec, several papers have reported results from field studies (Lechowicz and Jobin 1983;Mauffette et al 1983), but no laboratory tests on feeding preference have been conducted. In addition, factors such as drought stress of host plants and maternal effects on larval offspring, both of which are known to influence plant-insect interactions (Rossiter 1991;Mattson and Haack 1987), have not been investigated in the context of gypsy moth feeding preferences.…”
Section: Introductionmentioning
confidence: 99%